Eurasian Economic Union as a regional security and sovereignty strengthening factor - Zh.Y. Aubakirova; A.B. Aytbembetova; M.M Bigabatova (Хабаршысы. Экономика сериясы, 2016)
Eurasian Economic Union is a factor in the formation of the final stage of economic integration and strengthening of global and regional security. EAEU does not only generate an interest for cooperation experience from the neighboring countries, but it also encourages the integration processes within the framework of the Common Economic Space, which brings na-tional economies together into a single market and ensures the sovereignty and regional security of the Eurasian continent.